Tallas y otolitos en la determinación de la edad de la anchoveta Engraulis mordax (Pisces: EngrauUdae) - Chiappa-Carrara, Xavier (Universidad de Costa Rica, 1992)
Three populations of Engraulis mordax are differentiated in west Baja California coasts, on me basis of length frequency distributions and age-length relationsrups. Polymodal curve analyses according to Peternen,Cassie and Bhattacbarya determined foor age groops. Otelith analyses established eight age groops for caen populatioo in 1986 and 1987.Data obteined by Bhattacharya's memod were most similar te data determined by otolim anaIyses. The age-length relation snowed ibat individuals of me same age are larger in the northem thant in the soothem arcas